2015
DOI: 10.1194/jlr.m053678
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of full-length cholesteryl ester transfer protein in SW872 cells reduces lipid accumulation

Abstract: CETP is also present inside cells where two isoforms exist: full-length CETP, which is equivalent to plasma CETP, and exon 9-deleted CETP, a smaller form derived from alternatively spliced mRNA ( 6 ). The function of exon 9-deleted CETP is poorly understood. Overexpression studies suggest that exon 9-deleted CETP may bind to full-length CETP and hinder its secretion ( 6, 7 ), although this role was not supported by subsequent transgenic mouse studies ( 8 ).Multiple studies suggest that intracellular CETP modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 58 publications
2
34
1
1
Order By: Relevance
“…Interestingly, in preliminary studies, we observed that APOE mRNA levels in CETP-defi cient cells are only 5% of control levels. In contrast, cells overexpressing CETP, which also have decreased TG storage capacity, have normal APOE expression ( 11 ). It remains to be determined how suppressing CETP expression leads to reduced APOE expression, and whether a portion of the low TG phenotype in CETP-defi cient cells can be rescued by normalizing APOE expression.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Interestingly, in preliminary studies, we observed that APOE mRNA levels in CETP-defi cient cells are only 5% of control levels. In contrast, cells overexpressing CETP, which also have decreased TG storage capacity, have normal APOE expression ( 11 ). It remains to be determined how suppressing CETP expression leads to reduced APOE expression, and whether a portion of the low TG phenotype in CETP-defi cient cells can be rescued by normalizing APOE expression.…”
Section: Discussionmentioning
confidence: 96%
“…Much of the intracellular CETP pool is associated with the endoplasmic reticulum (ER), with increased concentrations near lipid droplets ( 8,11 ). Both cytoplasmic and lipid-droplet pools of CETP have been observed as well ( 11 ). Although the mechanism for CETP release into the cytoplasm is unknown, the escape of other ER luminal proteins to the cytoplasm has been reported (12)(13)(14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Androgen receptors are widely expressed in the Hd of zebrafish 27 , comparable to bpifcl expression identified in this study; this strongly suggests that testosterone could regulate Bpifcl modulation of kiss2 mRNA expression in the Hd of females. The BPIF family is known as a secreted protein 3 , 5 – 10 , however, several genes such as CETP 28 and PLTP 29 are also expressed in cytoplasm and nucleus. Especially, PLTP is suggested to be a modulator of signal transduction of the activation of the phosphatidylinositol-3 kinase/Akt pathway 29 .…”
Section: Discussionmentioning
confidence: 99%